Fun thinkers book and science textbook: Which is more effective in improving elementary school students' comprehension? - Muhammad Nizaar; Haifaturrahmah Haifaturrahmah (Universitas PGRI Madiun, 2023)
Science textbooks are widely available and accessible in elementary schools, often at no expense to students. However, evaluating and comparing their effectiveness with a visually engaging alternative, such as a fun thinkers book model that incorporates numerous illustrations, is necessary. Elementary school students exhibit a strong favor for images over text. This study aims to assess students' comprehension abilities utilizing the fun thinkers book and traditional science textbooks. This study employs a quasi-experimental design with a non-equivalent pretest-posttest control group design. The data collection method employed a test instrument to assess knowledge and practices related to waste management with an environmental theme. Data analysis employed an independent sample t-test to assess the statistical significance difference between the experimental and control groups. The findings indicated that the students who utilized the fun thinkers book exhibited a better understanding of waste management than those who relied on the textbook. Including pictures in the fun thinkers book enhanced the learning engagement of elementary school students, resulting in a higher level of comprehension than students who used the textbook alone.